THE PROSPECTS OF ASEAN ECONOMIC COMMUNITY (AEC) 2015 AS THE NEW ECONOMIC POWER IN ASIA - Mazia Rizqi Izzatika (2012)
his undergraduate thesis discuss about the ASEAN Economic Community (AEC), it is the major integration effort attempted in the developing world: it will create a single market with the free movement capital around nearly 600 million people. Every members of the Association of Southeast Asian Nations (ASEAN) will share benefits by this integration. There will be kind trade and investment diversion effects but the world as a whole will benefit from the AEC. In addition ASEAN has promoted multilate